Neurobiological Underpinnings of Obesity and Addiction: A Focus on Binge Eating Disorder and Implications for Treatment. - Balodis, Iris M.; Grilo, Carlos M.; Potenza, Marc N. (Psychiatric Times, 2015)
The article explores the neurobiological mechanisms behind obesity and binge eating disorder (BED) and their implications for treatment. Increased activity in the ventromedial prefrontal cortex/orbitofrontal cortex showed that people with BED are hypersensitive to motivational and rewarding properties of food. They also demonstrated reduced activity in frontal areas which are involved in cognitive control. Studies have shown that effective addiction treatments can be used to treat BED.